ANATOMICAL PATHOLOGY OF ASPERGILLOSIS AND RAILLIETINOSIS COMPLICATING CORYZA IN COMMERCIAL LAYERS HY-LINE BROWN IN RANCAEKEK, BANDUNG REGENCY - Amany, Nafisa Raihana; Guci, Rafika; Hartady, Tyagita; Khairani, Shafia; Windria, Sarasati; Wismandanu, Okta; Rosdianto, Aziiz Mardanarian; Satryo, Faisal Amri (Buletin Veteriner Udayana, 2023)
The aim of this study is to report a case of the upper respiratory system disease in chickens caused by the bacterium Haemopillus paragallinarum or what is known as infectious coryza (coryza/snot). This disease is an infectious disease in chickens that is acute to chronic. Observations made included anatomical pathology and bacterial isolation results. Poultry was necropsed and observed changes in the organs and then isolated them in media. The case study obtained was coryza disease which infected commercial laying hens of the Hy-Line Brown type, weight 1.2 kg, had brown feathers which were brought to the Padjadjaran University Teaching Veterinary Hospital with complaints of yellow caseous exudate in the left eye and Swelling of the infraorbital sinuses, nasal discharge, and shortness of breath. Physical examinations and supporting examinations were carried out in the form of necropsy examinations, endoparasite removal examinations, and fungal isolation and identification examinations in the case of chickens. On anatomical pathology examination, petechiae hemorrhage was found in the trachea, the lungs had interstitial pneumonia, liver discoloration became yellow, hemorrhage in the jejunum, findings of the endoparasite Raillietina spp. in the large intestine, ecchymatous hemorrhage in the caecum-colon, the kidneys are pale in color, and the ovaries experience oophoritis. Microbiological examination by isolating chicken comb samples showed the growth of Aspergillus niger spores. Based on the anamnesis, clinical symptoms, anatomical pathology, microbiological examination of fungal isolates, it was concluded that the chicken was diagnosed as having primary infectious coryza infection and secondary infections of raillietinosis and aspergillosis. Further supporting examination is needed by planting case animal sample isolates on chocolate agar media which has factors V and X, so that it can support the diagnosis of coryza.